Production and characterization of lipase from palm kernel cake using candida cylindracea and penicillium sp. by solid-state bioconversion - Elgharbawy, Amal Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Lipases are one of the most important classes in industry which catalyse hydrolytic as well as synthetic reactions. Increasing demand for lipases in the industrial and biotechnology applications has directed the researchers to produce lipase with cost effective method in large scale to meet the need. Thus, searching of optimal fermentation conditions with strain development (screening) and renewable waste as low cost basal medium for lipase production is gaining great interests as well as the waste reduction concept. One of the most abundant agro-industrial wastes in Malaysia is palm kernel cake (PKC). This study screened the ability of two different microorganisms to grow and produce lipase on PKC. The yeast, Candida cylindracea showed promising results and was selected to conduct further investigations. Screening and optimization for the parameters that affected the lipase production were studied using statistical experimental design including Plackett-Burman design where one-factor-at-a-time (OFAT) experiments were employed to find the optimal levels for optimization process. Response surface methodology (RSM) using faced centred composite design (FCCCD) was applied to study the interaction between the most contributing factors. The results showed that optimization process enhanced the lipase production in basal media of PKC supplemented with 1.5% (w/w) yeast extract, 2.0% (v/w) Tween-80, 0.5% (v/w) olive oil and 7.0% (v/w) inoculum at pH 7.0 and 30°C. Fermentation was carried out for 72 hours and maximum activity of lipase (400±2 U/g dry PKC) was achieved. The analysis of variance (ANOVA) indicated that the statistical model used was significant (p <0.05) with coefficient of determination (R2) of 0.9893 which was very close to the adjusted R2 (0.9816) which indicated the reliability of the model. Validation of the model was conducted using the optimal conditions mentioned previously where the predicted and the experimental results are in good agreement which prove the validity of the model and the existence of the optimal conditions. Productivity of the lipase as well as protein changes were studied to estimate the productivity as well as the optimal period for the fermentation. Production was the maximum at 72 hours with productivity of 4.93U/g.h. Characterization of the produced lipase revealed that temperature and pH optima were 37◦C and 8.0 respectively. The enzyme was stable at temperature ranges of 25-45◦C and pH 7.0-8.0. In metal ion solutions, Zn2+, Mg2+ and Ca2+ stimulated the enzyme while Fe3+ inhibited its activity. EDTA enhanced the lipase activity while incubation in SDS and Tween- 80 resulted in reduction of the activity. Moreover, the produced lipase exhibited some level of stability at low concentrations of organic solvents (methanol, ethanol, isopropanol, acetone, hexane and toluene).The application of lipase on lipid hydrolysis showed promising results where 50.84% of canola oil was converted to free fatty acids within 24 hours of the reaction and 45.98% of olive oil was hydrolysed. Based on this study, the bioconversion process of PKC can be considered promising in terms of economical aspect. Development of this process would be an alternative to future direction at large scale and cost-effective lipase production using PKC as a renewable raw material.